Research on the Impact of Wildlife Trade Based on a Linked Comparative Forecasting Model: A Case Study of ASEAN - Chen, Yuhua; Sun, Weifeng; Zhao, Xinyan (Transactions on Economics, Business and Management Research, 2024)
This study examines the challenges faced by ASEAN countries in combating illegal wildlife trade and implementing CITES. Despite efforts, illegal trade persists due to technological limitations, inadequate permit systems, poor interagency coordination, corruption, and low public awareness. The paper proposes project suggestions, including drone monitoring, a unified wildlife health information system, and improved enforcement mechanisms. Data analysis and empirical research confirm the alignment of these suggestions with ASEAN wildlife conservation plans. Predictions using linked models and ARIMA models suggest a high probability of successful illegal wildlife trade mitigation with adequate resources. The study provides a feasible approach for ASEAN to promote sustainable human-nature coexistence.